Analisis Faktor-Faktor Indeks Pembangunan Gender di Provinsi-Provinsi Pulau Sumatra Tahun 2011-2021 - Yolanda Putri Br Hutasoit, Hosiana Febby; Rozaini, Noni (Universitas Labuhanbatu, 2023)
This study aims to analyze the effect of life expectancy, per capita expenditure and average length of schooling on the Gender Development Index in the provinces of Sumatra island in 2011-2021. The Data used in this study is secondary data obtained from the Central Bureau of Statistics. This study uses panel data with cross-section data from a number of provinces in Java. Analysis of the data used is the KLA sik assumption test (multicollinearity test, heteroscedasticity test), and statistical tests (coefficient of determination test (R2), t test and F test) using the E-Views 9 application as an analytical tool. The results obtained that life expectancy has a negative effect and influence on the Gender Development Index, per capita expenditure has no effect and is not significant on the Gender Development Index, and the average length of school has a positive and significant effect on the Gender Development Index.